Pengaruh Health Promotion Terhadap Peningkatan Literasi Kesehatan “Perilaku Hidup dan Sehat” pada Siswa di Sekolah Menengah Pertama Kota Banjarmasin - Gertrudis Tutpai; Ermeisi Er Unja; Maria Frani Ayu Andari Diaz (INDO PUBLISHING, 2025)
Low health literacy leads to unhealthy behavior and the potential for long-term health problems. The school environment, as the primary place for character and knowledge formation, is a strategic location for implementing various health promotion programs. Improving health literacy through health promotion is one of the government's preventive programs. This study aims to evaluate the effect of health promotion programs on improving health literacy among junior high school students. This study used a quasi-experimental design with a pre-test and post-test approach without a control group. The sample consisted of 60 students using purposive sampling. The intervention carried out in this study was health promotion carried out by conducting interactive counseling on PHBS and how to wash hands properly with the help of educational media in the form of short videos. The instrument used in this study was a knowledge questionnaire regarding PHBS. The questionnaire has passed validity and reliability tests with Cronbach's values. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed an average knowledge score increase from 60.60 to 84.00 after the intervention, with a mean difference of 23.40 and a p-value of 0.000 (≤0.05). There was a significant difference between the level of family knowledge before and after the intervention. Health promotion interventions can improve health literacy related to clean and healthy living behaviors in school students. Schools should integrate health literacy materials into the school curriculum, particularly in science, physical education, and guidance and counseling.